Metabolic engineering of Propionibacterium freudenreichii subsp. shermanii for xylose fermentation. (November 2016) - Wei, Peilian; Lin, Meng; Wang, Zhongqiang; Fu, Hongxin; Yang, Hopen; Jiang, Wenyan; Yang, Shang-Tian
Highlights: P. freudenreichii cannot use xylose, the most abundant pentose in plant biomass. Xylose catabolic genes xylA, xylT, and xylB in P. acidipropionici were identified. They were overexpressed in P. freudenreichii subsp . shermanii . The engineered mutant can use xylose efficiently in the presence of glucose. The engineered P. shermanii can provide a novel cell factory for biorefinery. Abstract: Propionibacterium freudenreichii cannot use xylose, the second most abundant sugar in lignocellulosic biomass. Although Propionibacterium acidipropionici can use xylose as a carbon source, it is difficult to genetically modify, impeding further improvement through metabolic engineering. This study identified three xylose catabolic pathway genes encoding for xylose isomerase ( xylA ), xylose transporter ( xylT ), and xylulokinase ( xylB ) in P. acidipropionici and overexpressed them in P. freudenreichii subsp . shermanii via an expression plasmid pKHEM01, enabling the mutant to utilize xylose efficiently even in the presence of glucose without glucose-induced carbon catabolite repression. The mutant showed similar fermentation kinetics with glucose, xylose, and the mixture of glucose and xylose, respectively, as carbon source, and with or without the addition of antibiotic for selection pressure. The engineered P. shermanii thus can provide a novel cell factory for industrial production of propionic acid and other value-added products from lignocellulosic biomass.